2016
DOI: 10.2106/jbjs.15.00811
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Lateral Collateral Ligament Repair

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 27 publications
0
10
0
5
Order By: Relevance
“…8 Several studies have turned to arthroscopy to circumvent some of these issues. 3,8,9 Kim et al 10 reported the results of arthroscopic LUCL repair in 13 patients with a mean age of 25 years, all of whom had posterolateral rotatory instability after simple elbow dislocation. At the time of final follow-up, at a minimum of 18 months, all 13 patients reported complete resolution of the instability and mean (SD) extension of 3 (1 ), flexion of 138 (6 ), supination of 88 (5 ) and pronation of 87 (6 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies have turned to arthroscopy to circumvent some of these issues. 3,8,9 Kim et al 10 reported the results of arthroscopic LUCL repair in 13 patients with a mean age of 25 years, all of whom had posterolateral rotatory instability after simple elbow dislocation. At the time of final follow-up, at a minimum of 18 months, all 13 patients reported complete resolution of the instability and mean (SD) extension of 3 (1 ), flexion of 138 (6 ), supination of 88 (5 ) and pronation of 87 (6 ).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these complications, the arthroscopic approach has emerged as a safe and effective means for a wide range of acute and chronic elbow pathologies. Some studies report several advantages of arthroscopic management of elbow fractures, including improved visualization, better wound healing, preservation of soft tissue, and opportunity for early motion, thereby minimizing complications resulting from stiffness [ 11 , 12 , 19 , 20 ]. The most important advantage of arthroscopic management over open procedures is that it offers an appropriate view of the articular surface without damaging the surrounding soft tissue [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…An anterolateral portal was created using a spinal needle, and the FiberWire (Arthrex, Munich, Germany) was then transferred from the radial head portal to this portal for fixation at the LCL complex footprint. The FiberWires were fixed using one knotless anchor suture on the articular side of the LCL complex footprint of the humeral attachment [ 11 , 12 ]. After surgery, the joint was rendered immovable for approximately 2 to 3 days using a splint, which was later replaced with an elbow hinged brace to allow a phased joint movement.…”
Section: Methodsmentioning
confidence: 99%
“…Con una presión en varo sobre el antebrazo puede abrirse la articulación un poco más, lo que permite ver una mayor proporción de la superficie articular de la cabeza radial. En el caso de una apertura excesiva con una amplia visualización de la cabeza radial se debe valorar una insuficiencia del ligamento colateral lateral (4) . La inspección de las estructuras articulares nos permitirá diagnosticar cuadros clínicos de lesiones condrales (Figura 12) o artrosis en sus diferentes estadios, así como la presencia de osteocondritis, más típica en el capitellum (Figura 13).…”
Section: Compartimento Anteriorunclassified
“…Posterolateralmente, se delimita por la cápsula articular y superficial el ligamento colateral lateral (4) , medialmente por el cúbito y la articulación ulno-humeral, y distalmente por el repliegue sinovial capsular que cubre la porción posterior del ligamento anular.…”
Section: Gotiera Lateral O Compartimento Posterolateralunclassified